A qualitative exploration of patient and carer perspectives on pancreatic exocrine insufficiency due to pancreatic cancer. Issue 3 (1st September 2016) - Muircroft, Wendy; Gooden, Helen; Collier, Aileen; Carey, Sharon; Gott, Merryn; Currow, David
Abstract : Pancreatic exocrine insufficiency (PEI) is a condition that commonly occurs due to pancreatic cancer and is known to cause weight loss and have a negative impact upon quality of life. The purpose of this qualitative study is to explore patient and carer perspectives on the experience of PEI in pancreatic cancer and gain a better understanding of the implications of treatment. Semi-structured interviews were conducted with 14 patients and 9 carers recruited from palliative care and medical oncology services in the Adelaide region. Sampling continued until saturation of key themes. A critical thematic analysis was conducted. The study findings corroborated the findings from a previous study in quality of life and pancreatic cancer 1 and also extended clinical knowledge on the impact of the symptoms that patients and carers described. The presence and severity of PEI may be underestimated by using the presence of weight loss, steatorrhoea and abdominal pain to the clinical syndrome of PEI. Where patients and carers described treatment failure with pancreatic enzyme replacement therapy, new findings gave explanations for this. The results from this study suggest that further research needs to be done to compare the traditional clinical model assessing the presence of PEI in pancreatic cancer with a systematic approach to evaluation to increase the accuracy of clinical diagnosis, accessibility of treatment and monitoring of therapy. Reference: Gooden HM, White KJ.Pancreatic cancer and supportive care – pancreatic exocrine insufficiency negatively impacts on quality of life. Support Care Cancer 2013;27 (7):1835–1841